2009
DOI: 10.1177/1038411108099293
|View full text |Cite
|
Sign up to set email alerts
|

Human capital reporting: Should it be industry specific?

Abstract: Boards are exploring ways to report the value of intangible assets to investors. This paper explores human capital reporting and notes human capital is not reported within or between industry sectors in a standardised way. As a further development in a suite of models, we propose a framework, the Star Model, as a step in the standardisation of interpreting and reporting on human capital to investors. In developing this model, the authors question whether human capital reports should be industry specific, given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…These firms therefore cannot invest substantially in their employees. The varying human capital levels among different industries reflect the capital drivers of value that vary across industry groups (O'Donnell et al, 2009).…”
mentioning
confidence: 99%
“…These firms therefore cannot invest substantially in their employees. The varying human capital levels among different industries reflect the capital drivers of value that vary across industry groups (O'Donnell et al, 2009).…”
mentioning
confidence: 99%
“…Literature survey confirmed that HCD is gaining prominence (Adams et al, 2013;Huang et al, 2013;Motokawa, 2015;O'Donnell et al, 2012), especially since the adoption of integrated reporting that encourages the voluntary disclosure of information pertaining to HC. The three HCD sub-dimensions included HR planning and recruitment (7 items), remuneration, benefits and performance (6 items) and training and development (5 items).…”
Section: Human Capital Disclosure Constructmentioning
confidence: 99%
“…HCD regarding plans to maximise the value of people's embodied assets is useful for predicting future business returns (Magau, Roodt, & Van Zyl, 2021). Disclosed information on the implementation of key human resource (HR) practices such as workforce planning, recruitment, selection, development, performance and rewards can signal the companies' utilisation of HC for creating shareholder value (Adams et al, 2013;Motokawa, 2015;O'Donnell, Kramar, & Dyball, 2012). Huang, Luther, Tayles and Haniffa (2013) confirmed that when information about HR planning and recruitment is disclosed in the annual reports, it conveys the company's potential to create value, whereas the disclosure of information about remuneration practices is required in terms of King IV on corporate governance, IFRS and as part of the Johannesburg Stock Exchange (JSE) listing requirements (Cassim & Madlela, 2017;Kim & Taylor, 2011).…”
Section: Intellectual Capital Disclosurementioning
confidence: 99%
See 1 more Smart Citation
“…However, these new rules are applied to the companies with more than 500 employees, including listed companies as well as other public-interest entities, such as banks, insurance companies etc., including approximately 6 000 large companies and groups across the EU (European Commission, 2015). Therefore, for most companies the disclosure of non-Þ nancial information remains voluntary as there are only a few obligatory requirements for such disclosures, which is also conÞ rmed by the studies of Wyatt and Frick (2010) and O'Donnell et al (2009), stating that across various industries, human capital is not reported in a standardized way. It should also be noted that still many companies Þ nd CSR and HC reporting too costly and time-consuming with no immediate beneÞ ts to the company.…”
Section: Introductionmentioning
confidence: 99%